Pathways enabling educational success for vulnerable immigrants in Switzerland, Canada and France - Imdorf, Christian [Verfasser]; Koomen, Maarten [Verfasser]; Meyer, Thomas [Verfasser]; Kamanzi, Canisius [Verfasser]; Murdoch, Jake [Verfasser]; Guégnard, Christine [Verfasser] (My University, 2014)
This paper analyses the causes for educational success of students from vulnerable immigrant groups in France, Switzerland and Canada. It defines educational success as getting enrolled in a higher education program after completion of upper secondary education. The main research question is which educational pathways enable educational success for first and second generation immigrants in France, Switzerland and Canada, and what the underlying mechanisms are. Using statistical analysis (multinomial logistic regressions), three models are used to explain the different educational pathways to higher education in the three countries: immigrant status (model 1), early individual school characteristics (e.g. grades, reading skills, competence levels, etc., depending on country specific education system and available variables, model 2), and social background, gender, and aspirations (model 3). (BIBB-Doku)
Keywords: P 1.5 Migranten; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; T 1.5 International vergleichende Berufsbildungsforschung; Ausbildungsabsolvent; Migrant; Hochschulzugang; Durchlässigkeit im Bildungssystem; Internationaler Vergleich; Schweiz; Kanada; Frankreich